APPLICATION OF THE NUMBERED HEADS TOGETHER LEARNING MODEL WITH VIRTUAL LABORATORY SUPPORT ON WRITTEN COMMUNICATION - Setyono, Joko Wahyu (JURNAL SPEKTRA, 2024)
Science education in the era of globalization is now adapting to 21st-century skills. One rarely implemented stage is the communication stage. One of the aspects is the ability of students to communicate in writing. The main reason for this is the lack of attention given by teachers to the students' written communication skills. To enhance the written communication skills, the NHT (Numbered Heads Together) cooperative learning approach is employed. Since physical laboratory spaces may not always be available, practical activities can be conducted with the assistance of virtual laboratory applications. This research aimed to investigate the implementation of the NHT learning model supported by virtual laboratory tools in improving written communication skills related to the topic of simple machines among 8th-grade junior high school students. The results of the study revealed that the overall average score for all aspects in the NHT class with virtual laboratory support was 88%, indicating a "very good" performance category. On the other hand, the average score for all aspects in the scientific class was 82%, falling into the "good" category. The t-test results indicated a significance value (2-tailed) of 0.037, indicating a significant difference in the written communication abilities of students between the class using the NHT learning model with virtual laboratory support and the scientific class, specifically in the context of simple machines